Psychological well-being and exercise addiction: The treatment effects of an REBT intervention for females. (January 2023) - Knapp, Sarah; Miller, Anthony; Outar, Leon; Turner, Martin
Abstract: Whilst there is growing research on the benefits of Rational Emotive Behaviour Therapy (REBT) for athletic performance and wellbeing, there has been little attention on the effectiveness of REBT for the exercising population. Recent evidence suggests that REBT may be helpful for males who show signs of exercise addiction, but the effects for females are currently unknown. The current study aims to build on the extant research by adopting a single-case research design to examine the effects of REBT on irrational beliefs, exercise addiction symptomology, psychological distress, and unconditional self-acceptance (USA) of three female exercisers. Self-report data were collected at pre-, during, and post-REBT timepoints. Visual analyses revealed reductions in irrational beliefs and psychological distress, and increases in USA, maintained two-weeks post-REBT. Exercise addiction symptomology also reduced during the intervention, and this was maintained for two out of the three exercisers post-REBT. Social validation data supported these findings. The study adds weight to the efficacy of REBT in improving exercise addiction and its comorbidities. Highlights: REBT is effective for improving aspects of an individual's life that are affected negatively by their exercise routine. Rehearsing rational beliefs could play a role in improving flexibility for females at risk of exercise addiction. Psychological wellbeing of females at risk of exercise addiction can be improved through the application of REBT.